2016
DOI: 10.1177/1099800416648207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biochemical and Anthropometric Factors on the Presence of Insulin Resistance in Adolescents

Abstract: Background: Insulin resistance plays a determinant role in the development of metabolic syndrome in adolescents. The objective of the present study was to determine the influence of factors commonly associated with insulin resistance in a sample of adolescents. Methods: This cross-sectional study included 976 adolescents from southeast Spain. Anthropometric and biochemical measurements were performed, and insulin resistance was assessed using the homeostasis model assessmentinsulin resistance (HOMA-IR). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
8
2
Order By: Relevance
“…This underscores the importance of BMI and WC for predicting IR and is in accordance with our study results. Results of a cross-sectional study led by González-Jiménez et al showed that subjects with abnormal HOMA-IR values had significantly higher BMI, body fat content, and WC, and multivariate logistic regression analysis showed the highest OR for BMI, [ 19 ] which is consistent with our study results. Results from a study of Korean high school students showed that HOMA-IR was significantly associated with BMI and WC in both sexes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This underscores the importance of BMI and WC for predicting IR and is in accordance with our study results. Results of a cross-sectional study led by González-Jiménez et al showed that subjects with abnormal HOMA-IR values had significantly higher BMI, body fat content, and WC, and multivariate logistic regression analysis showed the highest OR for BMI, [ 19 ] which is consistent with our study results. Results from a study of Korean high school students showed that HOMA-IR was significantly associated with BMI and WC in both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported the correlation between the obesity index and IR, but some results have been inconsistent. [ 16 19 ] Samouda et al [ 16 ] demonstrated that adding the body fat distribution score to the BMI can improve the prediction of cardiometabolic, inflammatory, and adipokines profiles. This underscores the importance of BMI and WC for predicting IR and is in accordance with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our mediation analysis reinforces the relevance of adiposity as an important indicator of IR and diabetes risks. We also highlight that some measures of adiposity are considered simple, non-invasive, and low-cost methods that can be used to classify children, adolescents, and adults at risk of developing metabolic disorders, including IR and diabetes (Aristizabal et al 2015;Gonz alez-Jim enez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of waist circumference in defining obesity instead of BMI-SDS is also emphasized in recent literature [ 8 , 23 , 29 , 30 ]. In the studied population, only in adolescents, waist circumference was associated with IR.…”
Section: Discussionmentioning
confidence: 99%